Robot-assisted laparoscopic surgery after placing a self-expanding metallic stent for malignant rectal obstruction: a case report - Hiroshi Takeyama; Katsuki Danno; Takahiko Nishigaki; Masafumi Yamashita; Masami Yamazaki; Tsuyoshi Yamakita; Akihiro Nishihara; Hirokazu Taniguchi; Masayo Mizutani; Itsuko Nakamichi; Mamoru Yura; Kimimasa Ikeda; et al. (Surgical Case Reports)
Abstract Background Approximately 20% of colorectal cancer patients show complete or incomplete bowel obstruction as an early symptom. Preoperative nonsurgical decompression such as placing a self-expanding metallic stent for malignant colorectal obstruction has been shown to be effective for reducing perioperative morbidity and mortality. However, there is a lack of published studies reporting robot-assisted laparoscopic surgery (RALS) after self-expanding metallic stent (SEMS) placement for malignant rectal obstruction (MRO). To our knowledge, this is the first report to do so. Case presentation An 80-year-old man with incomplete paralysis of the lower limbs as well as bladder–rectal disorder due to a spine fracture sustained in a fall accident 26 years ago presented with lower abdominal pain and vomiting. Abdominal multi-detector computed tomography revealed an obstructive rectal tumor with distended bowel on the oral side. Emergency colonoscopy was performed, and an SEMS placed. The patency of SEMS and decompression of the distended bowel was confirmed, and elective RALS was performed 29 days after SEMS placement. To our knowledge, this is the first report of RALS after decompression with SEMS placement for MRO. Conclusions RALS after SEMS placement is a safe and feasible therapeutic strategy for MRO.